The Case of Piruani: Contested Justice, Legal Pluralism, and Indigeneity in Highland Bolivia. Issue 1 (13th July 2021) - Doyle, Matthew
Abstract: The 2009 Bolivian constitution included provisions that establish a radical form of de jure legal pluralism by creating a parallel legal system that gives full recognition to the nonstate legal orders and forms of conflict resolution of Indigenous communities. This article examines how a land dispute within a Bolivian highland Indigenous community resulted in a disagreement between different local forms of political and judicial authority. This turned on the question of which authorities had the right to judge the case, the nature of justice and indigeneity, and the legal pluralism enshrined in the constitution. Analysis of this situation illustrates not only the internal tensions and paradoxical effects of this juridical project but also the potential limitations of any attempt to formally recognize legal plurality. [legal pluralism, Indigenous justice, usos y costumbres, plurinational state, Movimiento al Socialismo]